1999
DOI: 10.1073/pnas.96.8.4313
|View full text |Cite
|
Sign up to set email alerts
|

A MHC-encoded ubiquitin-like protein (FAT10) binds noncovalently to the spindle assembly checkpoint protein MAD2

Abstract: Recently a number of nonclass I genes were discovered in the human MHC class I region. One of these, FAT10, encodes a protein consisting of two domains with homology to ubiquitin. FAT10 mRNA is expressed constitutively in some lymphoblastoid lines and dendritic cells and in certain other cells after ␥-interferon induction. FAT10 protein expression is controlled at several levels including transcription, translation, and protein stability. Yeast two-hybrid screening of a human lymphocyte library and immunopreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(174 citation statements)
references
References 42 publications
(43 reference statements)
5
169
0
Order By: Relevance
“…system such as thymus, lymph nodes, fetal liver and spleen (Canaan et al, 2006;Lee et al, 2003;Liu et al, 1999;Lukasiak et al, 2008). The high expression of FAT10 in the thymus could be allocated to medullary thymic epithelial cells (mTECs) and it was shown that FAT10 modifies thymic T-cell selection, probably due to an altered peptide presentation on MHC class I molecules (Buerger et al, 2015).…”
Section: Fat10 In Adaptive and Innate Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…system such as thymus, lymph nodes, fetal liver and spleen (Canaan et al, 2006;Lee et al, 2003;Liu et al, 1999;Lukasiak et al, 2008). The high expression of FAT10 in the thymus could be allocated to medullary thymic epithelial cells (mTECs) and it was shown that FAT10 modifies thymic T-cell selection, probably due to an altered peptide presentation on MHC class I molecules (Buerger et al, 2015).…”
Section: Fat10 In Adaptive and Innate Immunitymentioning
confidence: 99%
“…A recent publication showed, that a high induction of FAT10 expression is also achieved by a synergistic treatment of HepG2 cells with TNF-␣ in combination with IL-6 (Choi et al, 2014). Upregulation of FAT10 expression induced caspase-dependent apoptosis in HeLa cells, renal tubular epithelial cells as well as mouse fibroblasts (Liu et al, 1999;Raasi et al, 2001;Ross et al, 2006). However, the role of FAT10 in apoptosis is contradictory because other publications showed a pro-survival role of FAT10 (Canaan et al, 2006).…”
Section: Fat10 In Adaptive and Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, FAT10 was found to interact with MAD2, a mitotic spindle checkpoint protein (Liu et al, 1999) that has been shown to be important for maintaining genome stability (Michel et al, 2001). Dysregulation of MAD2 has also been implicated in tumorigenesis (Michel et al, 2001;Wang et al, 2002;Li et al, 2003).…”
Section: Fat10 Is Negatively Regulated By P53mentioning
confidence: 99%
“…It contains two ubiquitin-like domains joined by a short linker and is 29% identical to ubiquitin at its N-terminus and 36% identical at the C-terminus. Role of FAT10 in cell-cycle regulation has been suggested by its ability to bind to MAD2, a spindle checkpoint protein (Liu et al, 1999). We recently reported that the FAT10 gene is upregulated in various cancers (Lee et al, 2003), implicating its role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 97%